The Effectiveness of Celebrity Endorsement in India - Surana, Rajni (2008)
Abstract The practice of celebrities being used for rendering services other than performing their actual job as either an actor or an athlete, such as endorsements has proliferated over time. Despite the cost and the risks involved with this technique of advertising, it is been used quite extensively in the present era. The instrument of celebrity endorsement has nowadays become a pervasive element in advertising and communication management. India as a country is known for loving its stars. The Indians idolize their boll wood actors and cricketers. The advertisers see this as an opportunity to grab and work on so as to expand their operations and promote their product. This dissertation focuses on examining the perception of these Indian Consumers about the celebrity endorsement process and the subsequent impact on their purchase decisions. This project begins with a literature review which provides an insight into the research done by the previous authors followed by the structure of the research method adopted to achieve the objective this study. In depth qualitative interview approach has been adopted to investigate the attitude of the consumer towards celebrity endorsement and how it affects their daily lives. The findings derived from analyzing the collected data unearthed some very interesting facts which have been summarised in the conclusion and also managerial implication relating to it has been discussed.